An enhanced gene function analysis platform for Gastrodia Elata integrating further omics data and analysis tools - Bingbing Pan; Jingjie Zhang; Jiangxin Yang; Hang Yang; Qi Pan; Panpan Zhu; Jun Li; Jiaotong Yang (BMC Plant Biology)
Abstract Gastrodia elata, the dried tuber of the Gastrodia orchid, is a valued traditional Chinese medicine with important medicinal and dietary benefits. The growing multi-omics data demands an updated platform to include the latest G.elata genome and transcriptome, thereby enhancing gene function analysis for researchers. In this study, we built co-expression network using four versions of the G.elata genome, incorporated the latest transcriptome data, and annotated genes with sequences from TAIR, Uniprot, NR, and Swisprot databases. GO and KEGG annotations were predicted using InterProScan and GhostKOALA, while gene families were identified with HMMER, iTAK, OrthoFinder, and KEGG annotations. We further completed the GelFAP v3.0 upgrade ( http://www.gzybioinformatics.cn/Gelv3 ), integrating results and adding tools like BLAST, Gene sets enrichment analysis, Extract sequence, JBrowse v2, multiple sequence alignment, DEG analysis, DEM analysis, primer design and heatmap analysis. Through this platform, we identified that the GeMYB4 gene may function as a potential suppressor of flavonoid biosynthesis. Additionally, the platform enabled the identification of GePAL1, a key gene in the phenylpropanoid pathway, which showed higher expression in G.elata f.glauca compared to f.elata and was co-expressed with other upregulated genes involved in phenolic compound biosynthesis. Using GeMYB4 and GePAL1 as cases, we demonstrate the utility of this platform. GelFAP v3.0 will aid in analyzing key genes related to the biosynthesis of secondary metabolites, stress response, growth and development, offering researchers enhanced resources for studying G.elata gene functions.